Comparative Analysis of Guided Discovery and Guided Inquiry Models: Their Impact on High School Students' Analytical Thinking Abilities - Anggun Faradila Sandi; Mashari; Anugrah Teguh Prasetyo (Future Space: Studies in Geo-Education, 2024)
The importance of analytical thinking skills is vital in 21st-century learning and is a high-level skill required in the 2013 geography curriculum. Therefore, this skill is necessary in geography education to prepare students for everyday life challenges. Efforts to influence it can be made through the guided discovery and guided inquiry models. Both models require students to actively participate in learning activities to acquire analytical thinking skills. The aim of this study is to compare these two models to determine which is superior in developing students' analytical thinking abilities. The researcher employed a quasi-experimental design with a posttest-only control group design. The research subjects were students of grade 11 IPS 1 as experimental class 1 and 11 IPS 2 as experimental class 2, with the research conducted at SMAN 8 Malang. Students' analytical thinking abilities were measured using 11 valid and reliable essay questions. Data analysis utilized an independent sample t-test. The t-test results showed a significance level of 0.034, which is less than 0.05, thus leading to the rejection of H0 and acceptance of H1. It is concluded that there is a difference in the analytical thinking abilities of experimental class 1 and experimental class 2 students. The results also indicate that the guided inquiry model is superior to the guided discovery model. This superiority is attributed to the hypothesis formulation stage in the guided inquiry model, which effectively enhances students' analytical thinking abilities.